Larval Host Plants of Selected Lepidoptera (Moths: Heterocera and Butterflies: Rhophalocera) of Urban Delhi - Paul, Monalisa (Indian Forester, 2020)
The study compiles the list of larval host plants of selected butterfly and moth species of Delhi. It is based on the direct field observations and secondary data records between February 2015 to March 2016 and April 2016 to March 2017. Data were collected in three distinct periods each year i.e. (a) Pre-monsoon (Mid-February to Mid-June: comprises spring and summer), (b) Monsoon (Mid-June to Mid-September), and (c) Post- monsoon (Mid-September to Mid-February: comprises autumn and winter). This study provides an overview of more than hundred native plants and agriculturally important crops of Delhi which are the food plants of the larval stages of 40 spp. butterflies and 29 spp. of moths respectively. This investigation can help in restoration of the native flora of Delhi which is being destroyed under the clutches of urbanization. Sustainable conservation for the larval host plants in the concerned areas provides a useful foundation for urban greenery.